Tindakan Infus dengan Tingkat Kecemasan Orangtua yang Memiliki Bayi dalam Perawatan di Ruang NICU Rumah Sakit - Idayati, I; Wahyuni, Dian Eka (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
Anxiety is the condition of the anxiety which looks very different on every person. Preliminary study shows that 12 from 15 samples in NICU RS.Mitra Husada states worry about the condition of his babies especially if being done infusion. The purpose of this study is to determine the relationship between the actions of infusion with anxiety levels of parents who have babies receiving care in the NICU RS.Mitra Husada. This study was an observational analytic study with a cross sectional approach with a large population of 160 and the number of sample 27. The subjects were parents of neonatal patients treated in the NICU room. The sampling technique used is consecutive sampling. The statistical test used is Kolmogorof-Smirnov test. The data collection tool is the Zung Self-Rating Anxiety Scale (SRAS) Questionare. Results showed that respondents who have a level of anxiety among mild, moderate, and weight is not much different from p value = 0.028. The final results of the study show that there is a relationship between the actions of an infusion with the level of anxiety of parents who have babies receiving care in the NICU RS.Mitra Husada. This study is expected to be taken into consideration of hospital in reducing parents anxiety by applying education to patient and family and procurement of PICC facility.